Winning Hearts and Minds through Development? Evidence from a Field Experiment in Afghanistan - Beath, Andrew (The World Bank, 2012)
In areas afflicted by civil conflict, development projects can potentially serve an important counterinsurgency function by redressing grievances of marginalized groups and reducing violence. Using a large-scale randomized field experiment in Afghanistan, this paper explores whether the inclusion of villages in the country's largest development program alters perceptions of well-being, attitudes toward government, and violence in surrounding areas. The results indicate that the program generally has a positive effect on all three measures, but has no effects in areas with high levels of initial violence. These findings demonstrate that development programs can buttress government support and limit the onset of insurgencies in relatively secure areas, but that their effectiveness is more constrained in areas where insurgents are already active